(untitled) (Fiep Bulletin - online, 2013)
The body in motion at its creative and emotional turmoil, is not allowed at school only during the "recreational" when the teacher watches and observes accurately, avoiding mixing their authority to such puerile games. It is a life long controlled it explodes. To us it is precisely this life, this movement that matter, and with whom we want to work because they are the only true expression of the child (LAPIERRE & AUCOUTURIER, p. 29, 1986). The teaching practices of professionals, aiming to stimulate hyperactivity in children at the stage of Child Rearing, are in agreement with the theoretical assumptions concerning the study in question? This study looks which the perception that professionals who work with Child’s Education have regarding the need for pedagogical practice for the infant psychomotor development. This is characterized as a qualitative research, the field of descriptive type. The research involved a sample of N = 21 (twenty-one) teachers of the Municipal Network for Education in Rio de Janeiro, who work with classes from Child Rearing, forming a group of volunteers, all teachers in the West City Rio de Janeiro. It was used as an instrument of research, a questionnaire previously developed, evaluated by three master teachers, and validated by them, seeking to verify the perception that professionals who work with Child’s Education have regarding the need for pedagogical practice to develop children’s psychomotor . It was then, as the questionnaires were analyzed, teachers apply in their practice some of the psychomotor aspects, but there is a lack of theory that Embase such practices, leading the group discente do many different activities, but without knowing what you’re doing, and how it serves to enhance the student from them or what was observed.